Kinetics of Oxidation of Triphenylarsine and Triphenylstibine by Hydrogen Peroxide - Chellamani, A.; Chidambaram, K.C.A.D. (Asian Journal of Chemistry, 2012)
The kinetics of oxidation of triphenylarsine and triphenylstibine (Ph3M; M = As, Sb) have been studied in 70% (v/v) and 95% (v/v) aqueous ethanol respectively. The reaction exhibits second-order kinetics, first-order each in Ph3M and Hydrogen peroxide. A mechanism analogous t the one proposed for the oxidation of triphenylphosphine has been suggested.